Length of Variable Numbers of Tandem Repeats in the Carboxyl Ester Lipase (CEL) Gene May Confer Susceptibility to Alcoholic Liver Cirrhosis but Not Alcoholic Chronic Pancreatitis - Fjeld, Karianne; Beer, Sebastian; Johnstone, Marianne; Zimmer, Constantin; Moessner, Joachim; Ruffert, Claudia; Krehan, Mario; Zapf, Christian; Njolstad, Pal Rasmus; Johansson, Stefan; Bugert, Peter; Miyajima, Fabio; et al. (PLoS ONE, 2016)
Carboxyl-ester lipase (CEL) contributes to fatty acid ethyl ester metabolism, which is implicated in alcoholic pancreatitis. The CEL gene harbours a variable number of tandem repeats (VNTR) region in exon 11. Variation in this VNTR has been linked to monogenic pancreatic disease, while conflicting results were reported for chronic pancreatitis (CP). Here, we aimed to investigate a potential association of CEL VNTR lengths with alcoholic CP.Overall, 395 alcoholic CP patients, 218 patients with alcoholic liver cirrhosis (ALC) serving as controls with a comparable amount of alcohol consumed, and 327 healthy controls from Germany and the United Kingdom (UK) were analysed by determination of fragment lengths by capillary electrophoresis. Allele frequencies and genotypes of different VNTR categories were compared between the groups.Twelve repeats were overrepresented in UK ACP patients (P = 0.04) compared to controls, whereas twelve repeats were enriched in German ALC compared to alcoholic CP patients (P = 0.03). Frequencies of CEL VNTR lengths of 14 and 15 repeats differed between German ALC patients and healthy controls (P = 0.03 and 0.008, respectively). However, in the genotype and pooled analysis of VNTR lengths no statistical significant association was depicted. Additionally, the 16-16 genotype as well as 16 repeats were more frequent in UK ALC than in alcoholic CP patients (P = 0.034 and 0.02, respectively). In all other calculations, including pooled German and UK data, allele frequencies and genotype distributions did not differ significantly between patients and controls or between alcoholic CP and ALC.We did not obtain evidence that CEL VNTR lengths are associated with alcoholic CP. However, our results suggest that CEL VNTR lengths might associate with ALC, a finding that needs to be clarified in larger cohorts.
EVALuna2:15257